Nonauthenticity of comfort or courage to be untimely - R. L. Kochnev (Омский научный вестник: Серия "Общество. История. Современность")
This article is a commentary and an additional study to translate into Russian the article of the American philosopher Charles Guignon «Authenticity» published in this journal. In the article specific character of comfort in philosophy point of view is considered. There is described connection between phenomenons authenticity and comfort